Penggunaan Ekstrak Daun Pepaya (Carica papaya) sebagai Insektisida Nabati terhadap Hama Ulat Daun (Spodoptera litura) pada Sawi - Doharni; Parmanoan Harahap; siti Hardianti Wahyuni (Journal Agro-Livestock, 2025)
This study aimed to examine the effect of papaya leaf extract (Carica papaya) in controlling leaf-eating caterpillar pests (Spodoptera litura) on mustard greens (Brassica juncea). The research was conducted in Muara Pertemuan Village, Mandailing Natal Regency, from November 2023 to February 2024. The method used was a Randomized Block Design (RBD) with five treatments and six replications, resulting in a total of 30 experimental units. The treatments consisted of A0 (control), A1 (papaya leaf extract 50 g/L water), A2 (100 g/L water), A3 (150 g/L water), and A4 (200 g/L water). The observed parameters included the number of plants infested by Spodoptera litura, the number of damaged leaves, and plant yield. The results showed that increasing the concentration of papaya leaf extract effectively reduced the number of plants and leaves infested by Spodoptera litura. The highest yield was obtained from the treatment with 200 g/L papaya leaf extract, with an average production of 5700 grams.